PERAN KOMUNIKASI ANTAR PRIBADI DALAM MEWUJUDKAN KEPRIBADIAN ANAK DENGAN MEDIA PERMAINAN SIMULASI PERAN DI PANTI ASUHAN SAKINAH - Amalliah Amalliah; Ria Yunita (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2021)
Forming or realizing a child's personality is not an easy thing and also a very difficult thing. Children will be formed personality indirectly from the environment around where they live and grow. At Sakinah Orphanage, the children of the orphanage don't get the love of their family because they don't have parents and family anymore. And Sakinah orphanage children rarely interact with other people outside because they have to obey the rules that apply in the orphanage. This will shape the child's personality to communicate less closely with administrators, friends. Family communication is important in the role of the child's personality, so role playing simulation games can provide positive things and increase children's creativity and interaction effects. With 8 methods of role playing, children will be bombed and directed to get to know other people's characters or professions or jobs that they usually encounter everyday. Raising the theme of daily activities makes children more familiar and creative and dares to give opinions and in particular can improve interpersonal communication between them.